Reconfigurable wideband to narrowband antenna using tunable EBG structure - A. Rahim, Mohamad Kamal (Springer Verlag, 2014)
In this paper, frequency reconfigurable electromagnetic band gap (EBG) structure that integrates with a wideband antenna is proposed. The EBG structure consists of a circular patch shorted to the ground plane and a secondary circular patch connected to the circular patch. Switches are positioned between the via and the ground plane and by controlling the state of the switch, the band-stop operation of the EBG can be activated or deactivated. In order to control the single and dual band-stop operation, another switch is place between the circular patch and the secondary circular patch. The EBG structure is then placed underneath the feed line of a wideband antenna. The antenna is capable of reconfiguring to three different frequency bands. The proposed antenna has the potential to provide useful features for the wireless communication applications.